Low-Cycle Variable Amplitude Fatigue Modeling of Top-and-Seat Angle Connections - Mander, John B.; Chen, Stuart S.; Pekcan, Gokhan (Engineering Journal, 1995)
A set of variable amplitude tests was performed on a commonly used type of semi-rigid connection: the top-and seat angle. Variable amplitude tests included incremental decremental and step tests to investigate the sequence effects on cyclic and low-cycle fatigue behavior for this class of beam column connection. The concept of an effective equi-amplitude plastic rotation is introduced as the characteristic measure of rotation history. It is shown that effective rotation is independent of load path when compared to companion constant amplitude test results. An energy based cumulative damage model is characterized in terms of energy-life and energy-rotation relationships. The proposed damage model is employed in fatigue damage prediction analysis and compared with the classical Miner's linear damage accumulation model coupled with the rainflow cycle counting method. The proposed energy based damage model implicitly incorporates the memory effects of the previous loading history and precludes the necessity of performing explicit cycle counting, and it is easily implemented into non-linear time-history analysis for seismic design and evaluation purposes.